Peningkatan Hasil Belajar Matematika Siswa Melalui Penerapan Pembelajaran Kooperatif Tipe Numbered Heads Together - Fitriana Yolanda (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2019)
This study aims to improve the learning process and improve mathematics learning outcomes for students of class VIII MTs YKWI Pekanbaru. This research is a classroom action research study consisting of two cycles. The subjects in this study were grade VIII MTs YKWI Pekanbaru, totaling 20 students. Observation and test sheets are used to collect data. The results of this study indicate that there is an improvement in the learning process and an increase in mathematics learning outcomes for students of class VIII MTs YKWI Pekanbaru on the subject matter of relations and functions. The improvement of mathematics learning outcomes of students increased from the basic score of 40% to the daily test I by 60% and to the daily test II by 70%. The conclusion of this study is the application of cooperative learning type Numbered Heads Together can improve the learning process and improve mathematics learning outcomes for students of class VIII MTK YKWI Pekanbaru on the subject matter of relations and functions.